Expectations of Industry from Technical Graduates:Implications for Curriculum and Instructional Processes - Tulsi, P. K.; Poonia, M. P. (Journal of Engineering Education Transformations, 2015)
Industry is operating in an environment characterized by high performance work culture, intense competition, emphasis on quality, value addition, diversification of products and services, and automation as a result of globalization. Industry requires job ready graduates. It has been found that (a) the employability of technical graduates is low, (b) the requirements of skill set vary from sector to sector, Â© technical knowledge and skills are considered to be important but soft skills (communication skills, self discipline, teamwork, willingness to learn, flexibility, creativity etc.) are considered to be more important for employability, (d) technical graduates lack higher order cognitive skills such as ability to analyze, logical reasoning, ability to evaluate and create, and ability to solve problems, (e) knowledge of computers and mathematics are essential for an engineer to succeed, and (f) teaching-learning processes must focus on higher order thinking skills, problem solving and creativity and evaluation processes must change accordingly. Technical education needs total revamping and changes need to be introduced in the various sub-components of the system. The paper deals with the strategies that can be used to improve the quality of curriculum and instructional processes, and collaboration with industry.